Colonic angiodysplasia in a 34-year-old Nigerian: A case report with a review of literature - Eboreime OO; Umeaku U; Uchendu OJ; Yovwin G; Nwajei IA; Sokoh AC; Chukwuebuni U (Ibom Medical Journal)
Angiodysplasia is an arteriovenous malformation characterized by abnormal, tortuous, dilated small blood vessels in the mucosa and submucosa. It commonly occurs in the colon. We report a case of angiodysplasia in a 34-year old Nigerian male, who presented with recurrent asymptomatic, massive lower gastrointestinal bleeding. At laparotomy, it was observed that from the sigmoid to the rectum above the peritoneal reflection looked abnormal; with dilated, thickened and turgid wall, and multiple discrete bluish sub-serous swellings all around the sigmoid colonic wall. Affected segment of the colon was resected. Histology showed features consistent with angiodysplasia. His post-operative condition was stable. He was discharged on the seventh post-operative day and one month follow-up has been uneventful. Conclusion: Angiodysplasia is a common cause of lower GI bleeding. It should be considered in cases of massive lower gastrointestinal bleeding due to non-neoplastic causes.